Food Politics: How the Food Industry Influences Nutrition and Health - MARION NESTLE (University of California Press, 2013)
In 2002, when the University of California Press first published Food Politics, the idea that food and beverage marketing might influence food choices seemed surprising and, to the food industry and its supporters, alarming. Food choices, the industry said, were entirely a matter of personal responsibility. Obesity was the evident result of poor dietary choices and too little physical activity. The solution to the obesity problem? Get a grip. As I explained in the 2007 edition of the book, personal choice erupted as the principal argument against Food Politics before it had even been published. In February 2002, two weeks before the book first appeared in stores, three anonymous individuals posted critical reviews on Amazon.com. The reviewers accused me of blaming the food industry for what ought to be a matter of individual free will. â€œNestle forgot a not-so-little thing called WILL POWER!â€ said the first review. â€œMarion Nestle, one of the foremost food nannies in this country, has produced a book that heaps the blame for obesity, diabetes, and heart disease on food producers, marketing executives, and even school principals. Everyone, it seems, is responsible for those love handles except for the very people who are carrying them around.â€ From the second reviewer: â€œIndividuals incapable of thinking for themselves will truly appreciate . . . Food Politics. [Hasnâ€™t the author] ever heard of personal responsibility, exercise, and appropriate dieting?â€ And from the third: â€œMarion Nestleâ€™s book â€˜Food Politicsâ€™ makes clear that the political system she favors is dictatorshipâ€” with her in command. . . . The authorâ€™s motto could be â€˜if it tastes good donâ€™t eat it.â€™ â€